(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The Daugava or Zapadnaya (Western) Dvina River belongs to the Baltic Sea basin. The length of the river is 1,005 km with a drainage area of 87,900 km2. It crosses three countries: Russia (323 km and 18,500 km2), Belarus (328 km and 33,100 km2) and Latvia (352 km and 24,700 km2). Water samples were collected at three points with the following coordinates: Kraslava, Daugavpils, and Riga and distance from the river mouth 320, 255, and 20 km respectively. Discharge measurements by use of acoustic Doppler current profiler (ADCP) from a moving boat were also performed in the locations indicated above. Nitrates were extracted from water samples using the ‘ion-exchange resin method’, which involves extracting NO3- from freshwater and converting it into solid silver nitrate, which is then analysed for 15N/14N and 18O/16O ratios by IRMS. Prior to passing water through an anion-exchange resin precipitation of O-bearing contaminants (mainly sulphate and phosphate) with barium chloride was carried out. The δ15NNO3 values of riverine samples varied from 7.1 to 8.6 ‰ in Kraslava, from 7.2 to 8.3 ‰ in Daugavpils, and from 8.1 to 9.0 ‰ in Riga and displayed significant differences between the three sampling points.